Covid-19, Stigma & Law of the Leper - Kofi Gokah, Theophilus (International Journal of Global Health, 2021)
COVID-19 also known as Corona Virus is a new strain of Chronic Obstructive Pulmonary disease. While its virology is yet to be properly understood, its impact by way of human deaths is well registered. Stigma of infected persons is least mentioned as a ‘sub-strain’ that can push people into social isolation and exclusion (like in the book of Leviticus 13) leading to COVID-19 Related Depression (C-19RD). Using inter-disciplinary approach, this paper seeks to understand how this can happen in a COVID-stricken world.
Keywords: Public Health & Covid-19; Stigma; Social Media; Behaviour & Labelling theory Functionalism; Leviticus; Interactionism